“Obtención de dos poblaciones mejoradas de sacha inchi (plukenetia volubilis L.), con resistencia de meloidogyne incógnita mediante selección masal estratificada a partir de dos accesiones promisorias en la región San Martín” - Saboya Chávez, Carlos Alfredo (2015)
The sacha inchi (P/ukenetia vo/ubilis l.), is a soybean of the Euphorbiaceae family that is commonly known as mani of del monte, sacha mani or mani of the inca (Manco, 2004). Presents high levels of protein, vitamin E and unsaturated fatty acids (Hamaker, valleys, Gilman, Castro, Valdivia and Rodriguez, 1992;) Guillén, Ruiz, Cape, Chirinos and Pascual, 2003; Merino, Sotero, del Castillo and Vasquez, Cachique, Vasquez-Ocmín, 2008; Gutierrez, pink and Jimenez, 2011), which is considered an oil with low cholesterol content and beneficial to human health. The establishment of plantations of sacha inchi generates a positive environmental impact as it can be installed in surgery and degraded areas using tutors live and associate with legumes that revitalize degraded soils. The accessions of sacha inchi cultivated are susceptible to knot nematode (I / oidogyne incognita) and damage affects negatively the production, being a threat to...